Epineural glomus tumor of the posterior interosseous nerve: Case report. (April 2020) - Drabent, Philippe; Bielle, Franck; Bernat, Isabelle; Peyre, Matthieu
Highlights: Glomus tumors are exceedingly rare tumors arising from the normal glomus body. They are reported in subungual regions of digits but may involve peripheral nerves. Epineural nerve glomus tumors may mimick peripheral nerve schwannomas. Abstract: Among peripheral nerve sheath tumors, epineural glomus tumors represent a rare differential diagnosis for peripheral nerve schwannoma, displaying the same appearance on MRI. Here we present the case of a 68-year-old man complaining of pain in the left forearm, with paresthesias in the first three fingers. MRI demonstrated a round mass along the course of the posterior interosseous nerve with homogeneous contrast enhancement. Complete surgical removal successfully relieved the symptoms. Pathological analysis led to the diagnosis of glomus tumor of uncertain malignant potential . This is to our knowledge the first reported case of epineural glomus tumor of the radial nerve.